Minocycline hepatotoxicity: clinical characterization and identification of HLA-B∗ 35:02 as a risk factor - Urban, Thomas Jacob; Nicoletti, Paola; Chalasani, Naga; Serrano, Jose; Stolz, Andrew; Daly, Ann K.; Aithal, Guruprasad P.; Dillon, John F.; Navarro, Victor; Odin, Joseph; Barnhart, Huiman X.; Ostrov, David; et al. (Elsevier, 2017)
Minocycline hepatotoxicity can present with prominent autoimmune features in previously healthy individuals. The aim of this study was to identify genetic determinants of minocycline DILI in a well-phenotyped cohort of patients. Methods: Caucasian patients with minocycline DILI underwent genome-wide genotyping and were compared to unexposed population controls. Human leukocyte antigen (HLA) binding of minocycline was assessed using AutoDock Vina. Results: Amongst the 25 cases, 80% were female, median age was 19 years and median latency from drug start to DILI onset was 318 days. At presentation, 76% had acute hepatocellular liver injury, median ALT 1077 U/L (range: 63 to 2333), median bilirubin 4.5 mg/dl (range: 0.2 to 16.7), and 90% had a +ANA. During follow-up, 50% were treated with corticosteroids and no subjects died or required a liver transplant. A significant association was noted between HLA-B∗35:02 and risk for minocycline-DILI; a 16% carrier frequency in DILI cases compared to 0.6% in population controls (Odds Ratio: 29.6, 95% CI: 7.8-89.8, p=2.5 x 10-8). Verification of HLA-B∗35:02 imputation was confirmed by sequence-based HLA typing. HLA-B∗35:02 carriers had similar presenting features and outcomes compared to non-carriers. In silico modeling studies support the hypothesis that direct binding of minocycline to this novel HLA risk allele might be an important initiating event in minocycline-DILI. Conclusion: HLA-B∗35:02 is a rare HLA allele that was more frequently identified in the 25 minocycline-DILI cases compared to population controls. If confirmed in other cohorts, this HLA allele may prove to be a useful diagnostic marker of minocycline DILI.